Holistic Approach to Quran-Based Social Responsibility for Realizing a Civil Society Analysis of Spiritual Values and Social Welfare - Edi Hermando; Vera Seftia; Siska Juliana Putri (Yayasan Adra Karima Hubbi, 2025)
This research examines social responsibility from a Qur'anic perspective as a basis for building a just and prosperous civil society. Using a descriptive-analytical approach, this research analyses Qur'anic values that emphasise the importance of justice, solidarity and compassion towards vulnerable groups, such as orphans and the poor. The Qur'an asserts that social responsibility is not only an individual obligation, but also a collective responsibility involving various institutions, including the state and society. This research explains the concept of al-islâh as an effort to improve social and environmental conditions, as well as the importance of social intelligence based on Qur'anic values. By utilising secondary data from various literatures, this research shows that the implementation of Qur'anic values in daily life can create a balance between social rights and obligations. In addition, Qur'anic values-based education is considered the key to forming a young generation that cares about social responsibility. This research is expected to make a significant contribution in developing a framework for realising a civil society based on divine values, as well as addressing contemporary social challenges. Thus, social responsibility in Islam becomes the main foundation in creating positive and sustainable social change, in accordance with the principles of justice taught in the Qur'an.